An adult female patient with single atrium and single ventricle undergoing appendectomy: A case report - Wu, Yu; Cai, Zenghua; Cheng, Jianzheng; Zhang, Bo; Wang, Guoji; Li, Wei; Zhang, Zaiwang (Frontiers in Cardiovascular Medicine, 2023)
Appendicitis is one of the common diseases, and appendectomy is one of the most commonly performed procedures. Single atrium and single ventricle are rare heart diseases, and very few patients survive to adulthood. We report a patient with single atrial and single ventricles undergoing appendectomy with transverse abdominis plane block and dexmedetomidine sedation anesthesia with smooth postoperative appendectomy.